Evaluation of the Efficacy of Spa Therapy on Pain and Quality of Life in Patients With Chronic Mechanical Neck Pain - Aycan TÜREL,; Özlem SOLAK,; Ümit DÜNDAR,; Hasan TOKTAŞ,; Ümit Seçil DEMİRDAL,; Volkan SUBAŞI,; Vural KAVUNCU, (Archives of Rheumatology, 2015)
Objectives: This study aims to evaluate the efficacy of spa therapy on pain and the quality of life in patients with chronic mechanical neck pain. Patients and methods: Seventy patients who applied to our outpatient clinic with chronic mechanical neck pain lasting for 12 weeks were included in the study. Patients were randomized either to spa therapy group (7 males, 28 females; mean age 43.08±9.76 years; range 26 to 66 years) or to exercise therapy group (5 males, 30 females; 46.45±9.65 years; range 27 to 65 years). Spa therapy group received a total of 15 sessions of thermal water, mud therapy, and classic massage to cervical region. Both exercise and spa therapy groups performed home exercise program once a day for 15 days. All the patients were evaluated before treatment, at the first week and at the third month after treatment, a total of three times. In each control; visual analog scale, global assessment of the patient (Patient’s Global Assessment and Physician’s Global Assessment), Neck Pain Disability Scale, and Nottingham Health Profile were assessed. Results: When the measurements at first week were compared to baseline, significant improvements were observed in all the parameters in both groups. However, the decreases in visual analog scale and Neck Pain Disability Scale at the first week after treatment were more significant in spa therapy group compared to exercise therapy group. We observed no statistically significant difference in all the parameters between two groups when the measurements at the third month were compared to baseline. Conclusion: The combination of spa therapy with exercise therapy is superior to exercise therapy alone in decreasing pain and improving functional capacity in the early period after treatment.